Effect of water stress and enhanced solar UV-B radiation (280-320 nm) on physiology, biochemical and antioxidant activity in Raphanus sativus L. - Shanthi, N; Pillathil, J P S M; Murugan, R; Murugesan, S (Plant Science Today, 2026)
Multiple stress factors are produced in the natural ecosystem as a result of global climatic shifts. The two most significant abiotic stress factors that have an impact on plant development are UV-B radiation and water stress. In this study, long-term UV-B radiation (4 hr/day) and well water conditions were applied to Raphanus sativus L. seedlings. Each unfavourable circumstance has a different effect on the plants’ physiological and biochemical mechanisms. There are numerous ways the plant reacts to stress, including improved antioxidant activity, stress avoidance and increased proline content. The photosynthetic pigment study found that, compared to control and combined stress, the individual stress increased the production of chlorophyll and carotenoids. The levels of anthocyanin and flavonoids in R. sativus plants were significantly affected by UV-B and drought when water stress and UV-B were employed independently. With increasing and decreasing chlorophyll pigment content, linked stress action on non-photosynthetic chemicals was more likely to occur. Proline levels were higher in water-stressed R. sativus plants. The particular activities of antioxidant enzymes raised the likelihood of plants succumbing to UV-B alone and water stress plants more than when both stress elements were applied together. Further research is necessary to understand the mechanisms that regulate R. sativus development in response to UV-B and drought stress, as well as the interactions between osmotic potentials, plant water and the activation of stress-associated proteins and adaptive osmolytes.